Pengaruh Current Ratio, Inventory Turnover Terhadap Harga Pasar Saham Pt. Astra Internasional - Ahmad Sanusi dan Muhammad Halilintar (Jurnal Manajemen FE-UB, 2016)
The purpose of this research is to know how the Current Ratio and Inventory Turnover against stock prices. the company has a number of factors. Factors – factors that affect the level of stock price movements, namely the internal factors and external factors. Internal factors also known as the fundamental factor is the factor that comes from within the company and can be controlled by management of the company. These internal factors related to income will accrue to the financiers of either dividends or capital gains those factors will influence the supply and demand of society on shares listed on the stock market. So that also affect the price of the shares of the company, would be an increase in the stock price or otherwise on the textile companies were listed on the Indonesia stock exchange.The results of this research show that simultaneously variable Current Ratio and Inventory Turnover effect significantly to Price Shares in PT Astra Interenasional Tbk. It is indicated with the calculation result obtained is the probability of the mean 0.05 0.0000 < significantly. The value of R 2 of  0.794324 or of 79.43%.